Coagulation of colloidal raw water with Kaolin for water/Siti Rahayu Mohamed - Mohamed, Siti Rahayu (2009)
The treatment of water depends on the source of supply and the amount of impurities it contains. Coagulation process is effective and important process for turbidity removal in a water supply system. However the presence of kaolin in raw water contributes to the failure of coagulation process at Sg. Serai Water Treatment Plant. This study focus on establishing the effectiveness of turbidity removal for raw water taken from Sg. Serai by using selected coagulants. It involved taking raw water sample from the inlet of water treatment plant located at Sg. Serai and jar test were conducted. The raw water samples were analysed by many series of jar test to determine the optimum dosage of selected coagulants to remove the turbidity. This study considers only two coagulants namely aluminium sulphate and PAC and evaluation of their performances only. It was found that the optimum dosage of aluminium sulphate is 15 mg/1 with 49 % of turbidity removal. The optimum dosage of PAC is 5 mg/1 with 64 % of turbidity removal. However in the case of pH adjustment, aluminium sulphate greatly removes the turbidity of the raw water as it achieved 94 % turbidity removal.